2009
DOI: 10.1177/0042098009351941
|View full text |Cite
|
Sign up to set email alerts
|

Happy People in Mixed-up Places: The Association between the Degree and Type of Local Socioeconomic Mix and Expressions of Neighbourhood Satisfaction

Abstract: The potential impacts that a range of social, economic, demographic and structural factors have on an individual’s level of perceived satisfaction with their neighbourhood continue to be an important focus of research interest. This paper concentrates on a specific feature of the neighbourhood satisfaction literature by considering the impact of local neighbourhood socioeconomic mix on satisfaction. It suggests that, if neighbourhood satisfaction is associated with strong and sustainable communities, then unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 40 publications
7
52
3
1
Order By: Relevance
“…Good schools and low crime rates (Harris, 2001;Parkes et al, 2002), accessibility (Baum et al, 2010;Parkes et al, 2002) and high shares of owner-occupied dwellings (Harris, 2001) are found to be related to higher satisfaction with the neighbourhood. Finally variables such as general appearance, noise (Baum et al, 2010;Parkes et al, 2002), dilapidated dwellings (Galster & Hesser, 1981) and deterioration (Harris, 2001) relate to residential satisfaction.…”
Section: Neighbourhood Level Determinants Of Residential Satisfactionmentioning
confidence: 98%
See 4 more Smart Citations
“…Good schools and low crime rates (Harris, 2001;Parkes et al, 2002), accessibility (Baum et al, 2010;Parkes et al, 2002) and high shares of owner-occupied dwellings (Harris, 2001) are found to be related to higher satisfaction with the neighbourhood. Finally variables such as general appearance, noise (Baum et al, 2010;Parkes et al, 2002), dilapidated dwellings (Galster & Hesser, 1981) and deterioration (Harris, 2001) relate to residential satisfaction.…”
Section: Neighbourhood Level Determinants Of Residential Satisfactionmentioning
confidence: 98%
“…Parkes et al (2002) find in England that in affluent, predominantly owner-occupied neighbourhoods owner-occupiers are more satisfied than renters, while in poor neighbourhoods with high shares of rented dwellings, renters are more satisfied. Baum et al (2010) study neighbourhood satisfaction in Australia and find that the share of social housing has a stronger negative effect on satisfaction for owner-occupiers than for public tenants. Van Ham & Feijten (2008) study the desire to leave the neighbourhood in the Netherlands and find that, especially home-owners want to leave neighbourhoods with high shares of rented dwellings.…”
Section: Group Differences In the Effects Of Other Neighbourhood Charmentioning
confidence: 99%
See 3 more Smart Citations